CANADIAN DEFENCE POLICY IN THE 21ST CENTURY: AN ASSESSMENT OF CAPABILITIES AND COMMITMENTS - Philippe Lagasse (The Journal of Intelligence, Conflict and Warfare)
On November 20, 2024, Dr. Philippe Lagassé presented Canadian Defence Policy in the 21st Century: An Assessment of Capabilities and Commitments for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed addressed the state of Canadian defence, focusing on current challenges, future prospects, and lingering issues in the Canadian Armed Forces (CAF).